MINDFULNESS SEBAGAI STRATEGI REGULASI EMOSI - Yusainy, Cleoputri; Nurwanti, Ratri; Dharmawan, Ignatius Ryan Jeffri; Andari, Riska; Mahmudah, Maria Ulfatul; Tiyas, Rizki Restuning; Husnaini, Baiq Hanny Muthia; Anggono, Calvin Octavianus (Jurnal Psikologi, 2018)
Research on emotional regulation has been dominated by a hedonist perspective, which argued that the existence of positive affects and the absence of negative affects is an indicator of optimal human functioning. Meeting hedonic needs, however, is not the only goal of emotional regulation. Emotional regulation can also facilitate the integrity of the personality-oriented function as a whole. Mindfulness as an emotional regulation strategy is escorted by attention to all that is taking place in the present moment with an attitude of acceptance, thereby facilitating person-oriented function by bringing emotional experiences towards neutrality. The effectiveness of brief induction of mindfulness in comparison with other strategies in Gross and Thompson’s (2007) Process Model of Emotion Regulation (i.e., reappraisal, distraction, suppression) and control condition was tested in this randomized-mixed design experiment (N = 260) through self-reported ratings of affective valence for 60 positive, neutral, and negative photographs. The effectiveness of mindfulness was equivalent to positive reappraisal for positive stimulus, but lower than positive reappraisal for negative stimulus. Suppression consistently demonstrated equality of effectiveness with mindfulness, while distraction was as equally ineffective as control condition. These complex dynamics of emotional responding between mindfulness and other emotional regulation strategies requires further exploration.